Crystal structure of the SPRY domain of human SPSB2 in the apo state. Issue 6 (17th June 2019) - Luo, Yanhong; Li, Kefa; Yang, Jinjin; Zhang, Danting; Zhou, Yuying; Kuang, Zhihe
Abstract : The apo structure of the SPRY domain of human SPRY domain‐containing SOCS box protein 2 (SPSB2) determined at 1.9 Å resolution shows that its inducible nitric oxide synthase (iNOS)‐binding site is highly preformed and that the C‐terminal His6 tag binds to a shallow pocket adjacent to the iNOS‐binding site, which may help in structure‐based and fragment‐based SPSB2 inhibitor design. Abstract : The SPRY domain‐containing SOCS box protein 2 (SPSB2) is one of four mammalian SPSB proteins that are characterized by a C‐terminal SOCS box and a central SPRY/B30.2 domain. SPSB2 interacts with inducible nitric oxide synthase (iNOS) via the SPRY domain and polyubiquitinates iNOS, resulting in its proteasomal degradation. Inhibitors that can disrupt SPSB2–iNOS interaction and augment NO production may serve as novel anti‐infective and anticancer agents. The previously determined murine SPSB2 structure may not reflect the true apo conformation of the iNOS‐binding site. Here, the crystal structure of human SPSB2 SPRY domain in the apo state is reported at a resolution of 1.9 Å. Comparison of the apo and ligand‐bound structures reveals that the iNOS‐binding site is highly preformed and that major conformational changes do not occur upon ligand binding. Moreover, the C‐terminal His6 tag of the recombinant protein binds to a shallow pocket adjacent to the iNOS‐binding site on a crystallographically related SPSB2 molecule. These findings may help in structure‐based and fragment‐based SPSB2 inhibitor design in the future.